2021
DOI: 10.1038/s41598-021-03521-3
|View full text |Cite
|
Sign up to set email alerts
|

MARC1 p.A165T variant is associated with decreased markers of liver injury and enhanced antioxidant capacity in autoimmune hepatitis

Abstract: The clinical picture of autoimmune hepatitis (AIH) varies markedly between patients, potentially due to genetic modifiers. The aim of this study was to evaluate genetic variants previously associated with fatty liver as potential modulators of the AIH phenotype. The study cohort comprised 313 non-transplanted adults with AIH. In all patients, the MARC1 (rs2642438), HSD17B13 (rs72613567), PNPLA3 (rs738409), TM6SF2 (rs58542926), and MBOAT7 (rs641738) variants were genotyped using TaqMan assays. Mitochondrial dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The second protective variant, MTARC1, was shown to have beneficial effects on hepatic steatosis and cirrhosis and to correlate with improved plasma liver tests and lipoprotein profile [12]. Our candidate gene study demonstrated the protective effects of MTARC1 p.A165T polymorphism on liver injury in patients with autoimmune hepatitis (AIH) [13]. A brief report from Luukkonen et al highlighted that individuals carrying the minor allele of the MTARC1 p.A165T polymorphism are characterized by higher blood phosphatidylcholine levels and decreased parameters of NAFLD severity as compared to carriers of the wildtype MTARC1 genotype [14].…”
Section: Introductionmentioning
confidence: 69%
“…The second protective variant, MTARC1, was shown to have beneficial effects on hepatic steatosis and cirrhosis and to correlate with improved plasma liver tests and lipoprotein profile [12]. Our candidate gene study demonstrated the protective effects of MTARC1 p.A165T polymorphism on liver injury in patients with autoimmune hepatitis (AIH) [13]. A brief report from Luukkonen et al highlighted that individuals carrying the minor allele of the MTARC1 p.A165T polymorphism are characterized by higher blood phosphatidylcholine levels and decreased parameters of NAFLD severity as compared to carriers of the wildtype MTARC1 genotype [14].…”
Section: Introductionmentioning
confidence: 69%
“…A protective effect of the mARC1 p.Ala165Thr variant against liver disease and changes to lipid metabolism were first published in 2020 by Emdin et al . (Emdin et al ., 2020, Emdin et al ., 2021) and has since been confirmed by the work of other groups in additional studies (Luukkonen et al ., 2020, Mann et al ., 2020, Parisinos et al ., 2020, Gao et al ., 2021, Ghodsian et al ., 2021, Janik et al ., 2021). It has consequently been suggested, that mARC1 could present a target for future NALFD or NASH therapies (Bianco et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the MARC1 gene has been associated with protection for all-cause cirrhosis and lower blood hepatic enzyme levels [ 9 , 27 , 28 ]. In this study, we did not find a significant association with hepatic enzymes (data not shown).…”
Section: Discussionmentioning
confidence: 99%